Rethinking healthcare building design quality: an evidence-based strategy - Grant R. Mills; Michael Phiri; Jonathan Erskine; Andrew Price (2015)
Healthcare buildings play a significant role in delivering healthcare services and outcomes (e.g. quality, suitability, cleanliness, patient experience, value for money and risk mitigation). However, the current diffusion of responsibilities in England between central government and healthcare trusts has created gaps and weaknesses in the evidence base, knowledge, skills and tools for creating and assessing healthcare building design quality. How can a national healthcare building design quality improvement strategy be created? This question is explored in relation to policy, strategy and organizational issues. Four evaluation studies and four action research studies indicate the complexity and responsibilities in defining a design quality improvement strategy. It is found that the interdisciplinary development of national standards and tools requires centralized investment to facilitate nationwide learning and improvements in evidence and outcomes. In addition, the inevitable health policy changes made by successive governments require a sustainable and strategic response. The creation and maintenance of capacity and capabilities will require a dedicated team of professionals and a wide interdisciplinary network of long-term contributors who are motivated by a long-term desire to improve healthcare building design quality.